Children Crossing Streets: The Cognitive Task of Pedestrians Across Nations - David C. Schwebel (Ubiquity Press, 2017)
Background: About 100,000 children die worldwide in pedestrian crashes, more than 90% of whom live in low- and middle-income countries (LMICs). However, most existing research on children's ability to cross the street is conducted in high-income countries (HICs). Objective: The present study discusses 4 ways pedestrian behavior in LMICs differs from that in HICs, influencing both children's ability to cross streets safely and adult efforts to train children in pedestrian safety. Findings: First, in many LMICs one cannot simply wait for a traffic gap that is large enough to permit crossing at a typical walking pace. Instead, pedestrians must enter traffic gaps they deem large enough to permit the oncoming driver to stop, slow, or swerve around them. Second, decisions in LMICs must be made very quickly to maximize safety. In many cases, pedestrians must anticipate how oncoming drivers will behave as a crossing is initiated. Third, multilane LMIC crossings sometimes involve separated decisions to cross each lane and then evaluate safety in the middle of the roadway rather than making a single decision to cross the entire span within a safe traffic gap. Last, children's short stature may substantially influence behavior in LMIC settings. When gaps are small and open spaces limited, the ability to see over oncoming vehicles and perceive them approaching, including how spread they are and at what speeds they are traveling, offers a distinct advantage to the taller pedestria. Conclusions: Taken together, it is concluded that safe child pedestrian engagement in LMICs is more complex, and may require more developed cognitive skill, than safe child pedestrian engagement in HICs.